2010
DOI: 10.3168/jds.2010-3136
|View full text |Cite
|
Sign up to set email alerts
|

Effects of microbial inoculants on corn silage fermentation, microbial contents, aerobic stability, and milk production under field conditions

Abstract: The present study aimed to investigate the effects of 2 corn silage inoculation strategies (homofermentative vs. heterofermentative inoculation) under field conditions and to monitor responses in silage variables over the feeding season from January to August. Thirty-nine commercial dairy farms participated in the study. Farms were randomly assigned to 1 of 3 treatments: control (nonactive carrier; Chr. Hansen A/S, Hørsholm, Denmark), Lactisil (inoculation with 1 x 10(5)Lactobacillus pentosus and 2.5 x 10(4)Pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
83
2
13

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(109 citation statements)
references
References 33 publications
(51 reference statements)
11
83
2
13
Order By: Relevance
“…It is also reported that LA is converted into AA with L. buchneri inoculation, and thus higher AA compared with LA can be obtained . The LD inoculant increased the contents of acetic and propionic acids compared with the control (Table 3), and is in line with the general findings of the effects of inoculation with L. buchneri (Kleinschmidt & Kung, 2006;Kristensen et al, 2010;Nkosi et al, 2012).…”
Section: Days Of Ensiling Phsupporting
confidence: 74%
See 2 more Smart Citations
“…It is also reported that LA is converted into AA with L. buchneri inoculation, and thus higher AA compared with LA can be obtained . The LD inoculant increased the contents of acetic and propionic acids compared with the control (Table 3), and is in line with the general findings of the effects of inoculation with L. buchneri (Kleinschmidt & Kung, 2006;Kristensen et al, 2010;Nkosi et al, 2012).…”
Section: Days Of Ensiling Phsupporting
confidence: 74%
“…The LD inoculation increased (P <0.05) silage pH compared with the control. It is well known that inoculation of LB to forages at ensiling may result in increased silage pH compared with untreated silages , Kristensen et al, 2010. In contrast, LB inoculation did not influence the pH in maize silage (Reich & Kung, 2010), but reduced that of potato hash silage compared with control (Nkosi & Meeske, 2010).…”
Section: Discussionmentioning
confidence: 73%
See 1 more Smart Citation
“…Embora a fermentação heterolática seja menos eficiente quando comparada à homolática, a melhor estabilidade aeróbia da massa ensilada representa grande vantagem na utilização de aditivos contendo cepas de BAL heteroláticas (KUNG; RANJIT, 2001;NISHINO et al, 2004;MENDES et al, 2008;KRISTENSEN et al, 2010;TABACCO et al, 2011;ÁVILA et al, 2012 …”
Section: Fungosunclassified
“…O uso de inoculantes a base de bactérias heteroláticas têm sido eficiente em controlar a população de leveduras, reduzindo a fermentação alcoólica na massa ensilada, e melhorando a estabilidade aeróbia tanto em silagens de milho (RANJIT; TAYLOR; KUNG, 2002;NISHINO et al, 2004;KRISTENSEN et al, 2010;TABACCO et al, 2011), como de cana-de-açúcar (SIQUEIRA et al, 2007;ÁVILA et al, 2008;MENDES et al, 2008;MAEDA et al, 2011;ÁVILA et al, 2012). Silagens de cana-deaçúcar aditivadas com L. buchneri têm mostrado redução de 50% na produção de etanol (1,9 vs. 4,1% da MS), 17% na perda de gases, 56% na perda total de MS e aumento de 64% na estabilidade aeróbia em relação às silagens não aditivadas (PEDROSO et al, 2002(PEDROSO et al, , 2005SIQUEIRA et al, 2007;MENDES et al, 2008).…”
Section: Introductionunclassified